Majlis Agama Islam Wilayah Persekutuan Menara Daruzzakah / Siti Nur Syafhiqah Mohd Razali ... [et al.] - Mohd Razali, Siti Nur Syafhiqah; Khalil, Khairul Adha; Aziz, Mohd Nizham; Mohd Nordin, Muhammad Amirul Asraf; zaharuddin, Syafiq Azraei (2015)
The problem according to the issues and problems cannot be solved by maintenance management Daruzzakah building. It also describes the option-related problems and specific proposals that might resolve this problem. There are also maintenance problems in every chapter. To get the buildings that survive in the long run, it is necessary to more regular maintenance and in accordance with the schedule set by the management. There are certain identified problem in this final project which involves the building function and cause disadvantages to the building. The problems must be solve to ensure full building functionality and full comfort to the occupancy of the building